2006
DOI: 10.1152/japplphysiol.00981.2004
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous carbohydrate oxidation during ultraendurance exercise

Abstract: The purposes of this study were: 1) to obtain a measure of exogenous carbohydrate (CHO(Exo)) oxidation and plasma glucose kinetics during 5 h of exercise; and 2) to compare CHO(Exo) following the ingestion of a glucose solution (Glu) or a glucose + fructose solution (2:1 ratio, Glu+Fru) during ultraendurance exercise. Eight well-trained subjects exercised three times for 5 h at 58% maximum O2 consumption while ingesting either Glu or Glu+Fru (both delivering 1.5 g/min CHO) or water. The CHO used had a naturall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
114
3
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(132 citation statements)
references
References 43 publications
9
114
3
6
Order By: Relevance
“…42 A decrease in cadence with cycling duration has also been observed and is of unknown cause. [44][45][46][47][48] Perhaps the decrease in cadence has to do with fatigue of the neural networks constituting the central pattern generators or perhaps changed output from these. Another possibility is that peripheral fatigue affects freely chosen cadence.…”
Section: Draftingmentioning
confidence: 99%
“…42 A decrease in cadence with cycling duration has also been observed and is of unknown cause. [44][45][46][47][48] Perhaps the decrease in cadence has to do with fatigue of the neural networks constituting the central pattern generators or perhaps changed output from these. Another possibility is that peripheral fatigue affects freely chosen cadence.…”
Section: Draftingmentioning
confidence: 99%
“…Although there are studies in the scientific literature that have observed muscle metabolism behavior in ultra-prolonged exercise, [4,5]. In our research we decided to evaluate muscular metabolism performance under conditions never previously investigated.…”
Section: Discussionmentioning
confidence: 99%
“…This capture is particularly important since blood flow to active muscles can increase up to twenty fold during intense exercise [17]. Initially, this process probably prevents a critical reduction of intramuscular glycogen reserves, since it increases in the same way as glyconeogenic activity in the liver [5]. However, during ultra-prolonged exercise glycemic levels would be significantly reduced if it were not for the glucose/fatty-acids cycle modulation known as the "Randle Cycle", which increases fattyacid oxidation due to the increase in fatty-acids supply at the cellular level [18].…”
Section: Glycogen Persistence In Ultra Marathon Athletes After Six Homentioning
confidence: 99%
“…La seconde raison est que les glucides exogènes, notamment le glucose et ses polymères, ont des effets ergogènes au cours de l'exercice prolongé . Burelle et al, 2006Burelle et al, , 1997Decombaz et al, 1985;Guezennec et al, 1989;Jandrain et al, 1993;Massicotte et al, 1994Massicotte et al, , 1986Massicotte et al, , 1989Massicotte et al, , 1990Slama et al, 1989), galactose (Burelle et al, 2006;Leijssen et al, 1995), saccharose Leese et al, 1996;Massicotte et al, 1996a), maltose (Hawley et al, 1992b), polymères de glucose (Guezennec et al, 1993(Guezennec et al, , 1989Jarvis et al, 1992;Johannsen et Sharp, 2007;Leese et al, 1996;Massicotte et al, 1989;Rehrer et al, 1992), triacylglycérols à chaîne moyenne (MCT) Satabin et al, 1987), ou à longue chaîne (LCT) (Satabin et al, 1987)], ou de mélanges de substrats exogènes [glucose + fructose Hulston et al, 2009;Jentjens et al, 2004b;Jeukendrup et al, 2006;Massicotte et al, 1996a;Riddell et al, 2001), glucose + saccharose (Jentjens et al, 2004c, glucose + fructose + saccharose (Jentjens et al, 2004a(Jentjens et al, , 2006, glucose + maltose (Jentjens et al, 2004c), glucose + lactate (Péronnet et al, 1997), glucose + MCT (Goedecke et al, 1999b;...…”
Section: Vue D'ensemble Des éTudesunclassified